Dispute resolution in the construction industry an evaluation of British practice - Gould, Nicholas, 1942- (Thomas Telford, 1999)
This title works its way through the spectrum of dispute resolution techniques, negotiation, mediation and conciliation, expert determination, adjudication, arbitration, litigation and more.
"A Department of the Environment Transport and the Regions Partners in Technology Research Project."
Keywords: Labor disputes -- Great Britain.; Construction industry -- Great Britain -- Employees.; elektronické knihy; electronic books